1992
DOI: 10.4319/lo.1992.37.1.0131
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium enhancement of dark carbon fixation and nitrogen limitation in symbiotic zooxanthellae: Effects of feeding and starvation of the sea anemone Aiptasia pallida

Abstract: The nutrient status of algae symbiotic with marine invertebrates is controversial. We assessed the nitrogen status of zooxanthellae symbiotic with the sea anemone Aiptasia pallida using NH,+ enhancement of dark C fixation; enhancement increases with N limitation in other microalgae. Freshly isolated symbionts obtained from laboratory populations of known feeding history and from field populations were assayed: NH,+ enhancement depended on the nutritional history of the host anemones. Zooxanthellae from well-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…This cycle indeed shows that, in starved corals, uptake rates measured over 12 h (daylight period) were comparable to those measured over 24 h (day and night incubation). This suggests that uptake by these animals and in our conditions was constant throughout the 24 h. Ammonium uptake in the dark has been demonstrated by a number of other studies (Muscatine and D'Elia 1978;Wilkerson and Trench 1986) and has been suggested to increase the rate at which carbon is fixed by the zooxanthellae in darkness (Cook et al 1992). However, in fed corals, uptake rates were four times lower when measured for 24 than 12 h. Two hypotheses might explain such a difference: (1) zooxanthellae stopped taking up ammonium during the dark period, and/or (2) well-fed animals might have excreted nitrogen during the night.…”
Section: Discussionsupporting
confidence: 73%
“…This cycle indeed shows that, in starved corals, uptake rates measured over 12 h (daylight period) were comparable to those measured over 24 h (day and night incubation). This suggests that uptake by these animals and in our conditions was constant throughout the 24 h. Ammonium uptake in the dark has been demonstrated by a number of other studies (Muscatine and D'Elia 1978;Wilkerson and Trench 1986) and has been suggested to increase the rate at which carbon is fixed by the zooxanthellae in darkness (Cook et al 1992). However, in fed corals, uptake rates were four times lower when measured for 24 than 12 h. Two hypotheses might explain such a difference: (1) zooxanthellae stopped taking up ammonium during the dark period, and/or (2) well-fed animals might have excreted nitrogen during the night.…”
Section: Discussionsupporting
confidence: 73%
“…Symbiotic sea anemones, like other symbiotic cnidarians, still need to feed. In fact, cessation of feeding by Aiptasia pallida was correlated with nutrient deficiency in the zooxanthellae (Cook et al 1988(Cook et al , 1992. Periodical meals are therefore a necessity for the symbiosis to remain healthy.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen acquisition and exchange are of great importance to corals due to the nutrient-poor water in which they exist (Cook et al, 1992;Grover et al, 2008;Rädecker et al, 2015), and symbiosis has been proposed to increase the efficiency of nitrogen utilization by both partners (Wang and Douglas, 1998). We detected an ammonium transporter in symbiotic Aiptasia that was not detected in aposymbiotic anemones (Table 2), supporting the role of symbiosis in nitrogen exchange.…”
Section: Nitrogen Metabolismmentioning
confidence: 99%